Dissolution susceptibility of some Paleogene Planktonic Foraminifera from ODP Site 1209 (Shatsky Rise, Pacific Ocean) - M. R. Petrizzo; B. De Bernardi; F. Felletti; G. Leoni; R. P. Speijer (The Journal of Foraminiferal Research, 2008)
A detailed, quantitative analysis of planktonic foraminiferal composition and shell fragmentation is presented for samples from Ocean Drilling Program Site 1209 (Leg 198, Shatsky Rise, Pacific Ocean) in a stratigraphic interval from the Paleocene/Eocene boundary, which is characterized by enhanced carbonate dissolution, to the base of the middle Eocene where no distinct dissolution layers are recorded. The aims are to evaluate whether the composition of the fossil Paleogene assemblage is representative of the original assemblage and to what extent it is influenced by carbonate dissolution. By comparing the absolute abundances of whole specimens and fragments of the three most common Paleogene genera (Morozovella, Acarinina and Subbotina), it is demonstrated that the percentage of foraminiferal fragments, identified to genus, is helpful in interpreting the paleoenvironment of fossil planktonic foraminiferal assemblages affected by marked carbonate dissolution. In addition, the absolute abundance of whole specimens and fragments of the three Paleogene genera collected at the Paleocene/Eocene boundary and in the Eocene reveal that, contrary to earlier suggestions, the spinose, asymbiotic, deep-dweller Subbotina is less resistant to dissolution than the muricate, symbiontbearing, surface-dwellers Morozovella and Acarinina. Distinguishing between primary and taphonomic signals in Paleogene planktonic foraminiferal assemblages will be an important challenge to overcome in order to better constrain paleoecologic and paleoclimatic signals of global significance.